2020
DOI: 10.3390/toxins12090591
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Aflatoxin B1 and Deoxynivalenol in a Rural Pakistan Population Using Ultra-Sensitive LC-MS/MS Method

Abstract: There are limited data on exposure to mycotoxins in Pakistan. Here, we measured exposure to deoxynivalenol (DON), a common contaminant of wheat, and aflatoxin B1 (AFB1), a known contaminant of rice, using biomarkers of exposure. Wheat (n = 195) and rice (n = 62) samples were analyzed for AFB1 and DON levels, and the corresponding urinary biomarkers were analyzed in urine samples from a rural population (n = 264, aged 4–80 years, male 58%) using ultra-sensitive liquid chromatography–tandem mass spectrometry. AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The World Health Organization (WHO), based on records of worldwide aflatoxicosis outbreaks and in vitro tests, considers that regular consumption of food contaminated with AFB1 at levels of 1 mg/kg or higher for a short period can cause acute intoxication in humans, while daily consumption of AFB1-contaminated food at a dose of 0.02-0.12 mg/kg body weight (BW) over 1 to 3 weeks can cause life-threatening aflatoxicosis (Benkerroum 2020). AFB1 has also been associated with growth impairment in children and suppression of immune function (Xia et al 2020). AFB1 is metabolized to AFM1 via hydroxylation, and AFM1 has been proposed as a biomarker for acute aflatoxin exposure, which is excreted in the feces, urine, and milk of lactating mammals, including humans (Mupunga et al 2016;Schrenk et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO), based on records of worldwide aflatoxicosis outbreaks and in vitro tests, considers that regular consumption of food contaminated with AFB1 at levels of 1 mg/kg or higher for a short period can cause acute intoxication in humans, while daily consumption of AFB1-contaminated food at a dose of 0.02-0.12 mg/kg body weight (BW) over 1 to 3 weeks can cause life-threatening aflatoxicosis (Benkerroum 2020). AFB1 has also been associated with growth impairment in children and suppression of immune function (Xia et al 2020). AFB1 is metabolized to AFM1 via hydroxylation, and AFM1 has been proposed as a biomarker for acute aflatoxin exposure, which is excreted in the feces, urine, and milk of lactating mammals, including humans (Mupunga et al 2016;Schrenk et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al assessed the probabilistic risk of dietary exposure to AFB 1 contamination in foodstuffs in Guangzhou, China, using the MOE method, and found that the range of MOE was 4020~50 [ 36 ]. Another study from Pakistan reported that MOE values for AFB 1 exposure in rice and wheat were 112.9~13.2 [ 37 ]. AFB 1 is a highly toxic and strongly carcinogenic contaminant, and it causes serious liver damage and is very likely to cause hepatocellular carcinomas (HCCs).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, free DON and DON glucuronides were analysed separately as well as combined after enzymatic deconjugation. In the studies of Brera et al (2015) , Solfrizzo et al (2014) and Xia et al (2020) , children were included additionally in the study population and Shephard et al (2013) requested their study participants to consume a traditional maize-based evening meal prior urine collection. These differences hamper the comparison of the obtained HBM data.…”
Section: Resultsmentioning
confidence: 99%